Handbook of microwave technology. - Ishii, T. Koryu (Thomas Koryu), 1927- (Academic Press, 1995)
The Handbook of Microwave Technology provides a reference resource for professionals in business and industry as well as science and engineering students. A compact, concise reference, the Volumes contain focused chapters complete with useful formulas, charts, graphs, tables, examples, and diagrams that are clearly explained and easily applicable to practical cases. Volume I: Components and Devices provides a comprehensive overview of the components and devices used in microwave circuits, including microwave transmission lines, resonators, filters, ferrite devices, solid state devices, transistor oscillators and amplifiers, directional couplers, microstripline components, microwave detectors, mixers, converters and harmonic generators, and microwave solid-state switches, phase shifters and attenuators. Volume II: Applications discusses consumer, industrial, biomedical, and chemical applications of microwave technology. It also covers microwave instrumentation and measurement, thermodynamics, and applications in navigation, law enforcement, and radio communication. * of Volume I * Includes coverage of numerous components and devices used in microwave circuits, including: * Microwave transmission lines * Resonators, filters, ferrite devices, solid state devices * Transistor oscillators and amplifers * Directional couplers and microstripline components * Microwave detectors, mixers, converters, and harmonic generators * Microwave solid-state switches, phase shifters, and attenuators * Key Features of Volume II * Discusses consumer, industrial, biomedical, and chemical applications of microwave technology * Covers microwave instrumentation and measurements * Includes applications in navigation, law enforcement, and radio communication.